Effect of constant or step-up ractopamine hcl (paylean) feeding programs on growth performance and carcass characteristics of late-finishing pigs - J Y Jacela; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 1,099 pigs (PIC 337 × C22; initial BW = 208 lb) were used to evaluate the effect of ractopamine HCl (RAC) feeding programs on growth and carcass traits of late-finishing pigs. Pigs were randomly assigned to 1 of 3 treatments balanced by average BW within gender. There were 14 pens per treatment and 26 pigs per pen. Treatments were a basal diet with: (1) 0 g/ton RAC for 28 d (control), (2) 0 g/ton RAC from d 0 to 7 and 4.5 g/ton RAC from d 7 to 28 (constant), and (3) 4.5 g/ton from d 0 to 14 and 6.75 g/ton from d 14 to 28 (step-up). Pig ADG, ADFI, and F/G were determined weekly, and carcass data were collected at the end of experiment. From d 0 to 7, step-up pigs had improved (P<0.04) ADG, ADFI, and F/G compared with pigs in all other treatments. From d 0 to 14, RAC-fed pigs, regardless of the feeding program, had greater (P<0.01) ADG and better (P<0.01) F/G than control pigs. From d 14 to 28, although pigs in both RAC-fed treatments had greater (P<0.01) ADG than control pigs, the step-up pigs had lower (P<0.05) ADG and ADFI than the constant-fed pigs. Regardless of the RAC feeding program, all RAC-fed pigs exhibited better (P<0.01) F/G than control pigs. From d 7 to 28, pigs fed the constant and step-up treatments exhibited greater (P<0.01) ADG and better (P<0.05) F/G than control pigs. However, when pigs fed the RAC-fed treatments were compared, step-up pigs had lower (P<0.01) ADG and ADFI but similar (P>0.27) F/G. Overall (d 0 to 28), ADFI (P = 0.15) was similar between treatments, but RAC-fed pigs had greater (P<0.01) ADG than control pigs, which led to improved (P<0.01) F/G. Pigs fed either RAC feeding strategy had similar performance overall. RAC-fed pigs had heavier (P<0.05) carcass weights and tended (P<0.10) to have greater yield than control pigs. Among the 3 groups, step-up pigs had the greatest (P<0.05) percentage lean, loin depth, and fat-free lean index as well as the lowest (P<0.01) backfat depth. The pigs fed either RAC program had greater (P<0.05) revenue than control pigs. Although feed cost was higher (P<0.01) in the RAC-fed pigs than in the control, income over feed cost tended (P<0.07) to be higher for RAC-fed pigs than for control pigs. In conclusion, feeding a constant level of 4.5 g/ton RAC for 21 d improved growth similarly to feeding the 28-d step-up program. However, the 28-d RAC step-up program resulted in additional improvement in carcass traits of late-finishing pigs.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Growth; Ractopamine HCl; Swine